ANALYSIS OF INCLUSIVITY IN ECONOMIC GROWTH AND FACTORS THAT REDUCE POVERTY LEVELS IN BALI PROVINCE - Muhammad Emil Fadila; ihsan tabah hadiyanto; Zidan ullayatalatof (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
4.50% to 5.30% (yoy), which has the potential to be higher than the 2022 growth of 4.84% (yoy). The increase in economic growth in the Province of Bali was mainly due to the increase in tourist visits, both domestic and foreign. Even so, the number of poor people in Bali Province in 2022 is still quite high, reaching 205.6 thousand people, causing social inequality. Therefore, the purpose of this study is to analyze inclusive economic growth and the Gini and Growth Index (IGP) factors that can reduce poverty rates in the Province of Bali. The population of this study is the Province of Bali which consists of Regencies/Cities. The data used in this research is secondary data obtained from the Central Bureau of Statistics (BPS) of Bali Province. In this study, tests were carried out using the Chow test, Hausman test, and the Langrange multiplier (LM) test as a first step. The data analysis technique used is panel data path analysis. The variables in this study include the Human Development Index (X1), Total Population (X2), and Unemployment Rate (X3). The results of the analysis show that the Human Development Index (X1) has a positive and significant effect on the poverty rate, Population (X2) has a positive but not significant effect, while the Unemployment Rate (X3) has a negative and significant effect on the poverty rate.